(untitled) (Phenomenology, Humanities and Sciences, 2024)
In this theoretical essay, a confrontation is proposed between the thought of Thomas Kuhn, especially his analysis of the scientist’s behavior and the epistemological matrices in The structure of scientific revolutions, and the phenomenological approach to the construction of knowledge, having as its center the ontological, methodological and epistemological situation of Psychology. It is developed as a theoretical and argumentative essay, which develops five main argumentative lines through the confrontation of Kuhn’s theses with those of authors of a phenomenological point of view. At first, we try to demonstrate how normal thought, analyzed by Kuhn, has the same structure of meaning as naturalism, which seeks to be critically analyzed from a phenomenological perspective. In a second moment, it is proposed that psychology does not portray a period of solving puzzles, of normal science, nor the stage of a “pre-paradigmatic science”, according to Kuhn’s diagnostic criteria; and that this approach is due to an attempt at an analogical foundation of Psychology, but which hides a philosophical prejudice. Derived from this point, in a third moment, it is shown how the assumption of the alleged unity of Psychology, as a reality or as a goal, or, even, of its technical success, veils the question of the foundations of Psychology. As a fourth argument, it analyzes how the disengagement between language and reality, or between concept and factuality, is usually read in terms of a “paradigm crisis” or “crisis of Psychology”, which, hypothetically, would require a therapy to correct the established problem. Finally, it is argued that this disengagement, on the contrary, motivates a “change of attitude” on the part of the theorist in Psychology and, thus, requires him to deal with the problem of fundamentals.